2020
DOI: 10.1038/s41598-020-63523-5
|View full text |Cite
|
Sign up to set email alerts
|

NusA directly interacts with antitermination factor Q from phage λ

Abstract: Antitermination (At) is a ubiquitous principle in the regulation of bacterial transcription to suppress termination signals. in phage λ antiterminator protein Q controls the expression of the phage's late genes with loading of λQ onto the transcription elongation complex halted at a σ-dependent pause requiring a specific DNA element. The molecular basis of λQ-dependent At and its dependence on n-utilization substance (nus) A is so far only poorly understood. Here we used solution-state nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(168 reference statements)
0
1
0
Order By: Relevance
“…It will be interesting to see in the future whether 82Q-like proteins act by mechanisms distinct from those observed for 21Q. Furthermore, it has been shown that λQ directly interacts with NusA [ 110 ], and it remains to be seen whether and how this interaction on a λQ-EC modulates NusA’s co-transcriptional RNA chaperoning activity.…”
Section: Modulated Rna Chaperoning Functions In Factor-modified Transcription Complexesmentioning
confidence: 99%
“…It will be interesting to see in the future whether 82Q-like proteins act by mechanisms distinct from those observed for 21Q. Furthermore, it has been shown that λQ directly interacts with NusA [ 110 ], and it remains to be seen whether and how this interaction on a λQ-EC modulates NusA’s co-transcriptional RNA chaperoning activity.…”
Section: Modulated Rna Chaperoning Functions In Factor-modified Transcription Complexesmentioning
confidence: 99%